Domo Farm 4.0. (3rd February 2020) - Angeloni, Silvia
The paper explains and discusses an innovative agricultural appliance, based on vertical farming and hydroponics. The innovative and smart model was launched by a brilliant woman, winner of several awards. Applying her engineering skills, the female entrepreneur has set up a modern company, where technology and agriculture are perfectly integrated in a sustainable way to prevent environmental negative and damaging effects. Recently, the company has developed an automatic hydroponic greenhouse appliance for empowering individuals to grow crops at home. The household hydroponic appliance is based on sensors and smart technologies. The environmental and economic benefits and potentiality of the innovative appliance are highlighted.